Telomere Length and Skin Cancer - Han, PhD, Jiali (North American Journal of Medicine and Science, 2010)
Telomere length in peripheral blood lymphocytes has emerged as a potential biomarker of aging and risk of age-related diseases such as cancers. However, telomere shortening is implicated in several aspects of tumorigenesis, including senescence, apoptosis, and genomic instability. Because of the distinct proliferative features of different cells, telomere length may play roles in both suppressing and facilitating carcinogenesis. Understanding this heterogeneity is key for the development of targeted cancer-preventative and -therapeutic interventions. We use skin cancer as one example to elucidate that distinct genetic constitutions among different types of cells and tissues evoke different DNA damage responses against telomere shortening and malignant transformation.